CNTs support 2D NiMOF nanosheets for asymmetric supercapacitors with high energy density. Issue 42 (13th October 2022) - Hu, Nianxiang; Liao, Jiang; Liu, Xueliang; Wei, Jinlong; Wang, Li; Li, Min; Zong, Naixuan; Xu, Ruidong; Yang, Linjing; Wang, Junli
Abstract : The NiMOF/CNTs composite with NiMOF nanosheets grows along the CNTs is synthesized with a one-step solvothermal method, and the NiMOF/CNTs//AC asymmetric supercapacitors provide a high energy density of 113.8 Wh kg −1 at 800.0 W kg −1 . Abstract : In addition to complex preparation and low-yield syntheses, attaining high energy density while maintaining high power density remains a significant challenge for supercapacitor applications in the field of energy storage. Herein, two-dimensional (2D) nickel-based metal–organic framework (NiMOF) nanosheets are grown around carbon nanotubes (CNTs) to form NiMOF/CNTs composite, which is synthesized via a one-step solvothermal method at various temperatures. Thereinto, the NiMOF/CNTs composite synthesized at 180 °C (NiMOF/CNTs 180) exhibits enhanced electrical conductivity for ion and electron transport due to the addition of the CNTs, as well as the highest specific capacitance due to the unique 3D vine-like structure, which provides abundant active sites for electrochemical reactions. Specifically, the NiMOF/CNTs 180 composite demonstrates outstanding electrochemical performance with high specific capacitance (1855.0 F g −1 at 1 A g −1 ) and an excellent capacitance retention of 87.7% at 10 A g −1, indicating a favorable rate performance. The NiMOF/CNTs 180//AC asymmetric supercapacitors (ASCs) device assembled with NiMOF/CNTs 180 and activated carbon (AC) has a high specific capacitance of 320.0 F g −1 at 1 A g −1 and a maximum energy density of 113.8 W h kg −1 at 800.0 W kg −1 . Therefore, the present work provides a handy and efficient synthesis strategy for supercapacitor devices with high energy density.